2014
DOI: 10.1002/ajmg.a.36805
|View full text |Cite
|
Sign up to set email alerts
|

Nosology and inheritance pattern(s) of joint hypermobility syndrome and Ehlers‐Danlos syndrome, hypermobility type: A study of intrafamilial and interfamilial variability in 23 Italian pedigrees

Abstract: Joint hypermobility syndrome (JHS) and Ehlers-Danlos syndrome, hypermobility type (EDS-HT) are two markedly overlapping heritable connective tissue disorders. The cumulative frequency of JHS and EDS-HT seems high, but their recognition remains an exclusion diagnosis based on different sets of diagnostic criteria. Although proposed by a panel of experts, clinical identity between JHS and EDS-HT is still a matter of debate due to unknown molecular basis. We present 23 families with three or more individuals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
67
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 35 publications
6
67
2
2
Order By: Relevance
“…EDS, and particularly JHS/ hEDS, predominantly affects women, with a relative prevalence of about 70%. 2 Our cohort was relatively small and composed of all women except for one man. Therefore, despite the finding of SFN in all patients, we cannot exclude sex-related differences.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…EDS, and particularly JHS/ hEDS, predominantly affects women, with a relative prevalence of about 70%. 2 Our cohort was relatively small and composed of all women except for one man. Therefore, despite the finding of SFN in all patients, we cannot exclude sex-related differences.…”
Section: Resultsmentioning
confidence: 99%
“…1 More recently, segregation studies introduced and demonstrated the overlap between hEDS and the joint hypermobility syndrome (JHS). 2 The diagnosis of EDS is confirmed by molecular tools in most types except JHS/hEDS, which remains a clinical diagnosis based on available criteria. 3 Pain is common in various EDS types, particularly JHS/hEDS, 4 and its pathogenesis is mostly unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 In the present case, EDS-HT, also called ''EDS type III,'' mimics joint hypermobility syndrome. 4,5 EDS-HT and joint hypermobility syndrome are clinically overlapping connective tissue disorders featuring generalized joint hypermobility, muscloskeletal pain, and minor skin features. 6 EDS-HT and joint hypermobility syndrome may constitute the same clinical entity and likely share the same genetic background, at least in familial cases.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations into their relationship are still ongoing. 2,4 In classic EDS, the causative genes are COL5A1 and A2, COL1A1 and A2, COL3A1, PLOD1, and ADAMTS2, while the causative gene of EDS-HT has not been mapped so far. 2 In EDS-HT, the hereditary form is thought to be autosomal dominant, and the female:male ratio is about 2:1.…”
Section: Discussionmentioning
confidence: 99%